Apoptosis signal-regulating kinase 1 (Ask1) deficiency alleviates MPP+-induced impairment of evoked dopamine release in the mouse hippocampus - Zhao, Fang; Li, Chuhan; Zhuang, Yinghan; Yan, Yan; Gao, Yanqin; Behnisch, Thomas (Frontiers in Cellular Neuroscience, 2024)
The dopaminergic system is susceptible to dysfunction in numerous neurological diseases, including Parkinson's disease (PD). In addition to motor symptoms, some PD patients may experience non-motor symptoms including cognitive and memory deficits. A possible explanation for their manifestation is a disturbed pattern of dopamine release in brain regions involved in learning and memory, such as the hippocampus. Therefore, investigating of neuropathological alterations of dopamine release prior to neurodegeneration is imperative. This study aimed to characterize evoked hippocampal dopamine release and assess the impact of the neurotoxin MPP+ using a genetically encoded dopamine sensor and gene expression analysis. Additionally, considering the potential neuroprotective attributes demonstrated by apoptosis signal-regulating kinase 1 (ASK1) in various animal-disease like models, the study also aimed to determine whether Ask1 knockdown restores MPP+-altered dopamine release in acute hippocampal slices. We applied variations of low and high-frequency stimulation to evoke dopamine release within different hippocampal regions and discovered that acute application of MPP+ reduced the amount of dopamine released and hindered the recovery of dopamine release after repeated stimulation. In addition, we observed that Ask1 deficiency attenuated the detrimental effects of MPP+ on the recovery of dopamine release after repeated stimulation. RNA sequencing analysis indicated that genes associated with the synaptic pathways are involved in response to MPP+ exposure. Notably, Ask1 deficiency was found to downregulate the expression of Slc5a7, a gene encoding a sodium-dependent high-affinity choline transporter that regulates acetylcholine levels. Respective following up experiments indicated that Slc5a7 plays a role in Ask1 deficiency-mediated protection against MPP+ neurotoxicity. In addition, increasing acetylcholine levels using an acetylcholinesterase inhibitor could exacerbate the toxicity of MPP+. In conclusion, our data imply that the modulation of the dopamine-acetylcholine balance may be a crucial mechanism of action underlying the neuroprotective effects of Ask1 deficiency in PD.